Thematic Module Analysis Based on PPK: Reviewed from Attraction and Practicality Aspects - Denna Delawanti Chrisyarani; Arnelia Dwi Yasa (Pancaran Pendidikan, 2018)
Quality teaching materials are materials that contain character values from good refraction for children. The purpose of this study was to analyze the practicality and attractiveness of the PPK-based thematic modules. The research method used in this study is quantitative descriptive. Subjects in this study were students and teachers of grade 4 elementary schools in using thematic modules based on PPK. The instruments used in this study were questionnaires. The results of this study were to determine the level of practicality and attractiveness of thematic modules based on the fourth grade PPK elementary school. It is hoped that through the results of the analysis, it can produce better quality PPK-based modules. Can help teachers use and develop different PPK-based modules to apply to students.